Effects of Product Differentiation Strategies on Organizational Competitiveness: A Case of EABL, Kenya - Maina, Peter Kiama; Kagiri, Dr. A Wairimu Kiragu (European Journal of Business and Strategic Management, 2016)
Purpose: Product differentiation is achieved by offering a valued variation of the physical product. Firms have come to realize that in order to provide value and win customers, there is need to quickly and accurately identify changes in customer needs, design and develop more complex products which would provide higher levels of customers support and service. The study sought to fill the existing knowledge gap by establishing the influence of product differentiation strategies in achieving competitive advantage in EABL. Methodology: The target population was 14 managers from different departments. The study adopted a semi-structured questionnaire to collect primary data. Descriptive statistics such as means, standard deviation and frequency distribution were used to analyze the data. Qualitative data, which was mainly gathered from open and close ended questions. The data was consolidated, interpreted and then analyzed through content analysis. Regression analysis helped the study to establish the statistical significance of product differentiation in achieving competitive advantage in EABL. Results: From the findings, there are has been a product process differentiation in EABL where observable characteristics of a product that are relevant to customers' preferences and choice processes are met. These include size, shape, color, weight, design, material, and technology. The pricing of the products influence achievement of competitive advantage, the different products offered by the company led to production of reliable service delivery channels, products being designed as per customer needs, thus reducing failure costs and that the company has reasonable charges. The study also established that product market differentiation affect competitive advantage positively. Unique contribution to theory, practice and policy: The study recommends that strategic leadership of the firm should consider adopting product differentiation as they are the most dominant generic strategies adopted by similar organizations.